PEMAHAMAN REMAJA DALAM PENYELENGGARAAN JENAZAH DI KENAGARIAN ANDIANG KEC. SULIKI KAB. LIMA PULUH KOTA - Vivi Wahyu Wulandari; Alimir Alimir; Darul Ilmi; Khairuddin Khairuddin (Universitas Pahlawan Tuanku Tambusai, 2022)
Organizing the funeral prayer is one of the fard kifayah laws imposed on every Muslim. Teenagers' understanding in organizing funeral prayers is expected to improve the social attitudes of teenagers in society and help teenagers remember death that can come at any time in accordance with Q.S Ali-Imran verse: 185. The problems found, the lack of knowledge of teenagers related to the implementation of funeral prayers. There are still many teenagers who are not aware of the importance of holding funeral prayers, there is a sense of lack of care and laziness to learn to know the virtues and magnitude of the rewards of holding funeral prayers. Therefore, the author is interested in examining how the understanding of teenagers in organizing funeral prayers in Jorong Kampuang Baru. This type of research uses descriptive qualitative research methods and is in the form of field research. The location of this research is in Jorong Kampuang Baru and the researchers took this location because here the researchers found problems that needed to be discussed and were important to research. The key informants are late teens and the supporting informants are parents and mosque imams. To collect data, the authors conducted observations, interviews and documentation. After the data is collected, data processing and analysis is carried out. Furthermore, testing the validity of the data by means of triangulation of data. There are still many teenagers who give statements that they do not understand the implementation of the funeral prayer properly. The level of desire and motivation of adolescents to understand the funeral prayer is very low. Teenagers are also less aware of the importance of understanding the implementation of funeral prayers in order to show devotion to people who have died. Parents and imams of the mosque also revealed that the understanding of youth in organizing funeral prayers was indeed very lacking. There are several factors that cause a lack of understanding of adolescents including the educational background of adolescents, lack of motivation and education from parents, lack of a sense of caring for adolescents, and lack of awareness of adolescents about the importance of holding funeral prayers. Keywords: Understanding, Youth, Funeral Services